2016
DOI: 10.3233/jpd-150762
|View full text |Cite
|
Sign up to set email alerts
|

APOE, MAPT, and COMT and Parkinson’s Disease Susceptibility and Cognitive Symptom Progression

Abstract: BACKGROUND Cognitive decline is well recognized in Parkinson's disease (PD) and a major concern for patients and caregivers. Apolipoprotein E (APOE), catechol-O-methyl transferase (COMT), and microtubule-associated protein tau (MAPT) are of interest related to their contributions to cognitive decline or dementia in PD. OBJECTIVE Here, we investigate whether APOE, COMT, or MAPT influence the rate of cognitive decline in PD patients. METHODS We relied on 634 PD patients and 879 controls to examine gene-PD su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 41 publications
5
52
0
1
Order By: Relevance
“…Although patients in that study underwent detailed neuropsychological assessments, association tests between the H1 haplotype and change over time in the other cognitive measures were not performed. In contrast, a recent longitudinal study of 246 PD patients from the Parkinson’s Environment and Gene Study observed no association between the MAPT H1 haplotype and change in MMSE score over time (Paul et al, 2016). We recently reported that the MAPT H1 haplotype was not associated with any of the PDCGC core cognitive variables in a PD cohort that largely overlapped with the one studied here (Mata et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Although patients in that study underwent detailed neuropsychological assessments, association tests between the H1 haplotype and change over time in the other cognitive measures were not performed. In contrast, a recent longitudinal study of 246 PD patients from the Parkinson’s Environment and Gene Study observed no association between the MAPT H1 haplotype and change in MMSE score over time (Paul et al, 2016). We recently reported that the MAPT H1 haplotype was not associated with any of the PDCGC core cognitive variables in a PD cohort that largely overlapped with the one studied here (Mata et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…Because APOE ε4 is known to influence cognitive performance in PD (Mata et al, 2014, Morley et al, 2012, Paul et al, 2016), we separately genotyped rs429358 on all subjects using a TaqMan assay as previously described (Mata et al, 2014) and analyzed the ε4 allele using the methods employed for all other common variants. After correction for multiple testing, APOE ε4 was not associated with any of the core cognitive variables (Supplementary Table 11).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For these participants, validated weights were applied to make scores comparable with the 30-point in-person interview [58]. For patients with an MMSE score ≥26, in-depth assessment of cognitive function was performed at the next two follow-up exams with a detailed neuropsychological battery that included tests of global cognition, executive function, language, memory, and visuospatial skills described in greater detail elsewhere [59, 60]. …”
Section: Methodsmentioning
confidence: 99%